Epiphytic bryophytes in the built-up area of Kyiv city (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
20 species of bryophytes are found in the built-up area of Kyiv city. Most of them are synanthropic. The most common bryophytes species were Orthotrichum pumilum, Pylaisia polyantha, Leskea polycarpa andCeratodon purpureuswhich dominated in bryophyte overgrowths on tree bark. According to the distribution of epiphytic bryophytes five zones with different anthropogenic impact were distinguished in Kyiv: compact city zone, areas along roadways with heavy traffic, green plantations of the apartment block, small parks and squares in the built-up area, parks and wood in the suburbs.
Keywords: epiphytic bryophytes, frequency, cover, Kyiv.